IFN Regulatory Factor 4 Controls Post-ischemic Inflammation and Prevents Chronic Kidney Disease - Lorenz, Georg; Moschovaki-Filippidou, Foteini; Würf, Vivian; Metzger, Philipp; Steiger, Stefanie; Batz, Falk; Carbajo-Lozoya, Javier; Koziel, Joanna; Schnurr, Max; Cohen, Clemens D.; Schmaderer, Christoph; Anders, Hans-Joachim; et al. (Frontiers in Immunology, 2019)
Ischemia reperfusion injury (IRI) of the kidney results in interferon regulatory factor 4 (IRF4)–mediated counter-regulation of the acute inflammatory response. Beyond that, IRF4 exerts important functions in controlling the cytokine milieu, T-cell differentiation, and macrophage polarization. The latter has been implicated in tissue remodeling. It therefore remains elusive what the role of IRF4 is in terms of long-term outcome following IRI. We hypothesized that an inability to resolve chronic inflammation in Irf4−/− mice would promote chronic kidney disease (CKD) progression. To evaluate the effects of IRF4 in chronic upon acute injury in vivo, a mouse model of chronic injury following acute IRI was employed. The expression of Irf4 increased within 10 days after IRI in renal tissue. Both mRNA and protein levels remained high up to 5 weeks upon IRI, suggesting a regulatory function in the chronic phase. Mice deficient in IRF4 display increased tubular cell loss and defective clearance of infiltrating macrophages. These phenomena were associated with increased expression of pro-inflammatory macrophage markers together with reduced expression of alternatively activated macrophage markers. In addition, IRF4-deficient mice showed defective development of alternatively activated macrophages. Hints of a residual M1 macrophage signature were further observed in human biopsy specimens of patients with hypertensive nephropathy vs. living donor specimens. Thus, IRF4 restricts CKD progression and kidney fibrosis following IRI, potentially by enabling M2 macrophage polarization and restricting a Th1 cytokine response. Deteriorated alternative macrophage subpopulations in Irf4−/− mice provoke chronic intrarenal inflammation, tubular epithelial cell loss, and renal fibrosis in the long course after IRI in mice. The clinical significance of these finding for human CKD remains uncertain at present and warrants further studies.